The legacy of M. N. Srinivas - Shah, A. M., 1931- author.
1 online resource
Keywords: "M. N. Srinivas is acclaimed as a doyen of modern sociology and social anthropology in India. In this book, A. M. Shah, a distinguished Indian sociologist and a close associate of Srinivas', reflects on his legacy as a scholar, teacher, and institution builder. The book is a collection of Shah's five chapter on and an interview with Srinivas, with a comprehensive Introduction. He narrates Srinivas' life and work in different phases; discusses his theoretical ideas, especially functionalism, compared with Max Weber's ideas; deliberates on his concept of Sanskritization and its contemporary relevance; and reflects on his role in the history of sociology and social anthropology in India. In the interview, Srinivas responds to a large number of questions: from the style of writing to the dynamics of politics. It shows while his scholarship was firmly rooted in India, it was sensitive to global ideas and institutions. This book will be an essential read for scholars and researchers in sociology, social anthropology, history, and political science. The general reader interested in these subjects will also find it useful"--